Effectiveness of colonic stent placement for obstructive colorectal cancers: An analysis of short‐term results using a nationwide database in Japan. Issue 7 (24th April 2022) - Moroi, Rintaro; Tarasawa, Kunio; Shimoyama, Yusuke; Kuroha, Masatake; Shiga, Hisashi; Kakuta, Yoichi; Fushimi, Kiyohide; Fujimori, Kenji; Kinouchi, Yoshitaka; Masamune, Atsushi
Abstract: Background and Aims: Self‐expandable metallic stent (SEMS) is widely used for obstructive colorectal cancer (OCC). Both SEMS and urgent surgery have several merits and demerits. This study aimed to clarify the efficacy of SEMS by comparing the mortality rate after the hospitalization between SEMS and urgent surgery for OCC. Methods: We collected OCC patients' data using the Diagnosis Procedure Combination (DPC) database system. We divided eligible patients into the SEMS and urgent surgery groups using propensity score matching and compared in‐hospital death rates, length of hospitalization, and medical costs. We also conducted logistic regression analysis to identify clinical factors affecting in‐hospital deaths. Results: We enrolled 17 140 cases after propensity score matching. SEMS reduced the in‐hospital death rate compared with urgent surgery (2.0% vs 3.6%, P < 0.0001). Length of hospitalization was shorter in the SEMS group than in the urgent surgery group (16 vs 25 days, P < 0.0001). Medical costs were lower in the SEMS group than in the urgent surgery group (1 663 550 vs 2 424 082 JPY, P < 0.0001). Multivariate analysis also showed that SEMS reduced in‐hospital death (odds ratio = 0.58, 95% confidence interval: 0.50–0.70, P < 0.0001). Conclusion: Self‐expandable metallic stent placement for OCC might reduce the mortality rate in short term and shorten the length of hospitalization. These results facilitate considering SEMS with careful judgment for its indication when treating OCC patients.